Genetic Variability, Heritability and Genetic Advance for Agronomic Traits in Field Pea (Pisum sativum L.) Gene Pools - Yimam, Kedir (International Journal For Research In Agricultural And Food Science, 2020)
A total of 49 field pea genotypes were grown in 7 x 7 simple lattice design at two environments in south-eastern highlands of Ethiopia during 2018/19 main cropping season to study genetic variability, heritability and genetic advance for grain yield and yield-related traits. The combined / pooled/ analysis of variance revealed that there was a significant difference (p< 0.001) among the 49 field pea genotypes for all the characters studied, except for number of seeds per pod, which was non-significant. High phenotypic coefficient of variation and genotypic coefficient of variation were recorded for grain yield, and moderate values for 1000-seed weight and plant height was observed across locations. Estimates of heritability ranged from 23.66 % for ascocayta blight to 90.73 % for days to flowering, while grain yield showed 63.18 % heritability. High genotypic coefficient of variation along with high heritability coupled with genetic advance as percent over mean was observed for grain yield per ha and moderate genotypic coefficient of variation along with high heritability coupled with moderate or relatively high value of genetic advance as percent over mean in plant height and seed size was observed across locations; indicating the importance of this trait in yield improvement of field pea.